2014
DOI: 10.1016/j.jchf.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of Serial Soluble ST2, Growth Differentiation Factor-15, and Highly-Sensitive Troponin T Measurements in Patients With Chronic Heart Failure

Abstract: In patients with chronic HF, baseline measurement of novel biomarkers added independent prognostic information to clinical variables and NT-proBNP. Only serial measurement of sST2 appeared to add prognostic information to baseline concentrations and predicted change in left ventricular function. (Use of NT-proBNP Testing to Guide Heart Failure Therapy in the Outpatient Setting (PROTECT)]; NCT00351390).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
4
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 18 publications
8
117
4
19
Order By: Relevance
“…Beside NP, more and more has been written about novel biomarkers related to cardiac remodeling and fibrosis. Gaggin et al 32 confirmed that sST2 appears to be a more useful biomarker than others, such as GDF-15 and galectin-3 in the population of patients with CHF. 33 In addition, the present study found that QRS duration is independently associated with sST2 levels.…”
Section: Discussionmentioning
confidence: 96%
“…Beside NP, more and more has been written about novel biomarkers related to cardiac remodeling and fibrosis. Gaggin et al 32 confirmed that sST2 appears to be a more useful biomarker than others, such as GDF-15 and galectin-3 in the population of patients with CHF. 33 In addition, the present study found that QRS duration is independently associated with sST2 levels.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the Seattle Heart Failure Model, the Penn Heart Failure Study found that a multimarker score incorporating biomarkers increased the ability to predict adverse outcomes in ambulatory patients with chronic HF (8). A post hoc analysis including 151 patients with chronic HF showed that baseline measurement of 3 biomarkers (ST2, growth/diff erentiation factor 15, and highly sensitive assay for troponin T) increased the overall prognostic ability, while serial ST2 measurement helped predict change in left ventricular function (9). In older patients with stable HF, soluble isoform of ST2 was found to be an independent predictor of worsening HF, suggesting an association between increasing values of soluble isoform of ST2 and progressive myocardial failure (10).…”
Section: Discussionmentioning
confidence: 99%
“…All these results indicate that sST2 is a useful biomarker in subjects with CHF. 5,6 GROWTh DIffERENTIaTION faCTOR 15…”
Section: Soluble St2mentioning
confidence: 99%